Toxoplasma gondii: 1908-2008, homage to Nicolle, Manceaux and Splendore - David J P Ferguson (Memorias do Instituto Oswaldo Cruz, 2009)
The discovery of Toxoplasma gondii independently by Nicolle and Manceaux (1908) and Splendore (1908) was to open a "Pandora's Box" that has led research on this parasite into a number of scientific disciplines. In the 100 years since its discovery, the mystery surrounding T. gondii and its inter-relationship with humans has continued to provide a stimulating source of material in many areas of research, resulting in the publication of almost 20,000 papers and a number of books. This flood of diverse information shows no sign of abating, with an average of 10 papers per week appearing in PubMed. Herein, it is impossible to do more than provide a very superficial comment on what has become a massive body of scientific information. T. gondii has many unique features and seems to be the "exception to almost every rule" thus acting as a focus for research in disciplines from epidemiology to immunology to human behaviour to cell biology to human disease. In this review a number of the historical advances will be mentioned and combined with a description of the basic biology of the parasite.